Market Knowledge and Responsiveness to Competitors Its Influence on Marketing Agility Mediated by Market Turmoil Variables (Case Study on Tile Producer MSMEs in Kebumen Regency) - Tiyan Fatkhurrokhman; Najmudin Najmudin; Sudarto Sudarto (Citakonsultindo, 2024)
This research aims to study the influence of market knowledge and responsiveness to competitors on marketing agility on MSMEs producers of strawberries in Kebumen district, as well as the role of market agitation mediation in the relationship. This research uses a quantitative method with a questionnaire distributed to the owner of MSMEs genteng in Kebumen district. The data obtained was analyzed using SPSS software to test the hypothesis put forward. Research data is obtained from questionnaires designed to gather information related to market knowledge, competitor responsiveness, marketing agility, and market turmoil. The respondents consisted of the owner of MSMEs producer of strawberries in Kebumen district. Research has shown that market knowledge and responsiveness to competitors have a significant influence on marketing agility. MSMESs with market knowledge and high responsiveness are better able to adapt and make quick decisions in the face of market dynamics, improving their marketing agility.